FACTORS ASSOCIATED WITH SELF-REPORTED ARBOVIRUSES IN AN AREA OF EXTREME SOCIAL VULNERABILITY IN BRASILIA, BRAZIL - Silva Martins, Ana Carolina; Andrade, Flávia Reis de; Obara , Marcos Takashi; Oliveira , Max Moura de; Gurgel-Gonçalves , Rodrigo; Cruvinel , Vanessa Resende Nogueira (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2024)
This study investigated the association of environmental, demographic, and socioeconomic factors in the poorest area in Brasilia, the capital of Brazil, with the occurrence of self-reported arboviruses. It is a cross-sectional study with a quantitative approach including sociodemographic variables, access to water and sanitation, sewage disposal and living habits. A survey created in Google Forms was sent via mobile phone to the heads of households who lived in the Estrutural area, which hosted the largest open dump in Latin America for almost 60 years. There were 2,176 responses, of which 1,934 (88.9%) were from women, 1,432 (65.8%) from those who had no partners, 961 (44.16%) were illiterate or had incomplete elementary school, and 1,155 (53.08%) reported having already had arboviruses. After the adjusted analysis, storing water in the residence (Odds Ratio - OR 1.58; CI 1.30-1.92), having knowledge on how to prevent arboviruses (OR 2.22; CI 1.61-3.06) and being a waste picker (OR 1.84; CI 1.46-2.31) showed a positive association with self-reported arbovirus, while waste collection was a protective factor (OR- 0.71; CI 0.63-0.92). The influence of occupational and environmental factors were observed with arboviruses. Effective intersectoral measures focused on this vulnerable population are needed in all sectors, including training them to face these diseases.